Dose-response and time-lagged effect of daily training load on athlete well-being during an international rugby series - Crewther, Blair T.; Serpell, Benjamin; Potts, Neill; Kilduff, Liam P.; Cook, Christian J. (Biology of Sport, 2025)
Rugby training and competition both impose a stress or training load (TL) affecting athlete wellbeing. Current understanding of the TL dose-response and time-lagged changes (i.e., delayed effects) in wellbeing is limited. We addressed these gaps using data from a 3-week international series. Twenty-two elite male rugby players were assessed 4–5 days a week for daily TL and well-being (i.e., mood, stress, soreness, fatigue, sleep quality). A distributed lag non-linear model was used to estimate the TL effect, at the within-person mean (358 A.U), +1SD (576 A.U) and +2SD (794 A.U), on well-being at 0–5 lag days. Average daily TL declined by -38% and -45% in weeks two and three (vs. week 1), respectively, with weekly fluctuations of +27% to -58% (vs. Monday training). The well-being subscales oscillated around a stable baseline. Compared to mean-centered scores, a significant decline in mood and sleep quality (-0.6 to -2.0 units; -9 to -30%) emerged at all TLs, with a delayed shift at higher loads. Elevated stress, soreness, and fatigue responses (up to 3.7 units; 76%) emerged with increasing daily TLs, including a biphasic rise in stress and fatigue at higher loads. In conclusion, we gained detailed insight into physical stress and the temporal sequence of well-being during an international rugby series. Different daily TLs predicted adverse well-being responses (i.e., declining mood and sleep quality, rise in stress, soreness, fatigue) that varied in lag timing, duration, and magnitude. Explicating these associations can assist weekly planning and strategies to optimize recovery, performance, and team success.